2017
DOI: 10.1007/s12560-017-9278-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of a GII.4 Norovirus Sydney 2012 Variant Equipped with GII.P16 RdRp and Its Predominance over Novel Variants of GII.17 in South Korea in 2016

Abstract: Noroviruses are major causative pathogen of nonbacterial acute gastroenteritis worldwide. Of the seven genogroups of noroviruses suggested recently, genogroup II genotype 4 (GII.4) had been the most common genotype identified in hospitalized patients in the last few decades. However, since the latter half of 2014, new variants of GII.17 have been reported as the main causes of outbreaks over GII.4 in East Asia and have also occurred in America and Europe. In this study, we monitored norovirus GII in coastal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…Interestingly, the GII.P16 sequences shared by GII.2 and GII.4 Sydney genotypes were nearly identical to the GII.P16-GII.4 Sydney sequences reported in Japan in January of 2016 (29) and in coastal waters impacted by sewage in China (44). GII.2, GII.3, GII.10, GII.12, GII.13, and GII.17 viruses are known to harbor GII.P16 polymerases.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the GII.P16 sequences shared by GII.2 and GII.4 Sydney genotypes were nearly identical to the GII.P16-GII.4 Sydney sequences reported in Japan in January of 2016 (29) and in coastal waters impacted by sewage in China (44). GII.2, GII.3, GII.10, GII.12, GII.13, and GII.17 viruses are known to harbor GII.P16 polymerases.…”
Section: Discussionsupporting
confidence: 53%
“…Here, we demonstrate that the emerging GII.P16-GII.4 Sydney 2012 norovirus lineage is circulating in the UK and USA, in addition to previous reports of circulation in Asia and Germany [6–8]. Analysis of available sequences suggests that this lineage has been circulating since October 2014 or earlier (Fig 2).…”
Section: Discussionsupporting
confidence: 79%
“…While the first five pandemic strains contained the GII.P4 RdRp, the most recent pandemic strain (Sydney 2012) circulated more commonly with the GII.Pe RdRp. Recent reports demonstrated circulation of the Sydney 2012 capsid with a GII.P16 RdRp in South Korea, Japan and Germany [6–8]. While the GII.P16 RdRp is not typically highly prevalent, a GII.P16-GII.2 virus was the dominant strain amongst a large peak of norovirus infections in Germany in Winter 2016 [8].…”
Section: Introductionmentioning
confidence: 99%
“…This seems contradictory; however, the predominance of GII.P16-GII.2 viruses in certain countries (20, 21) coincided with the detection of a novel GII.4 strain, GII.P16-GII.4_Sydney (20, 42–44), suggesting that this GII.P16 polymerase could have a positive impact on the fitness of the virus. Indeed, using the murine norovirus model, Arias et al have shown that the fidelity of the polymerase could influence the transmissibility of the virus (45).…”
Section: Discussionmentioning
confidence: 99%